Code-Switching by Teenagers from Jakarta - Roselin Putri Guntala (Linguistics Initiative, 2021)
There are numerous languages available around the world. The Indonesian language and English are just two of the many languages spoken around the globe. Aside from that, there are numerous regional languages spoken on Indonesia's various islands. As a result, Indonesians tend to move from Indonesian to their regional language (mother tongue). Furthermore, Jakartan youths frequently transfer from Indonesian to English and vice versa. The goal of this paper is to look into the code-switching that occurs among Jakartan youths. Many people transition their language from their mother tongue to their second language unknowingly. Similarly, some Jakartan teens discovered that their first language (Indonesian) was being replaced by their second language (English). This study was part of a qualitative research project that used a case study approach. To collect the necessary data, this study used observations and interviews as tools. When having a conversation with someone, the participants engage code-switching, according to the findings of this study. This is because speaking makes them feel more at ease and confident. When a person is fluent in more than one language, this is referred to as bilingualism or multilingualism.